Comparative analysis of National Ocean Strategies of the Atlantic Basin countries - Inês da Silva Marques; Conceição Santos; José Guerreiro; José Guerreiro (Frontiers in Marine Science, 2022)
In 2007 the European Union (EU) launched the Blue Book introducing the Integrated Maritime Policy (IMP) for the sustainable growth of the coastal regions of Member States. The IMP has several cross-cutting areas of intervention such as the Blue Growth Strategy, Maritime Spatial Planning, and Strategies for maritime basins. To ensure this policy’s implementation, the European Commission requested its coastal members to develop integrated maritime strategies. Furthermore, within the United Nations Decade of Ocean Science for Sustainable Development, it is also a priority of the EU to ensure compliance with the 2030 Agenda, in particular the SDG14. This study focuses on countries from the Atlantic Basin, namely France, Ireland, Portugal, Spain, and the UK (before Brexit) comparing key priorities and objectives of national ocean strategies of these countries and how they match IMP guidelines and the 2030 Agenda. The results show that one of the main focuses of these strategies is the mitigation and adaptation to climate change and nature conservation. On the other hand, desalination, exploration and prospection of oil and gas are the socioeconomic sectors of smaller significance. This study also demonstrated that Spain and UK’s ocean strategies cannot be considered as a national ocean strategy in the IMP concept. The national ocean strategy of Ireland was introduced almost 10 years ago, therefore can be considered outdated in several dimensions. France and Portugal are the only countries whose national ocean strategies are aligned with the objectives of the Atlantic Action Plan and the only ones that truly follow the guidelines of the EU Integrated Maritime Policy.